The Effectiveness of an Educational Program Based on the Threats and Opportunities of Remote Work for Dual-Career Couples During the COVID-19 Pandemic on Work-Family Conflict and Its Dimensions - Saeedtaleshi, Leyla; Shafie Abadi, Abdollah; Yousefi, Emad (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The purpose of this research was to evaluate the effectiveness of an educational program based on the threats and opportunities of remote work for dual-career couples during the COVID-19 pandemic on work-family conflict and its dimensions. Method: This was a quantitative, applied research employing a quasi-experimental design, utilizing a pre-test/post-test with a control group. The sample consisted of dual-career couples from Kerman city who sought counseling for various reasons. Collaboration was negotiated with a private counseling center, and agreements were made. Couples scoring above the cutoff on the prepared questionnaires were purposively selected, resulting in 20 couples who were then randomly assigned to either the experimental group (10 couples) or the control group (10 couples). The experimental group underwent the educational program while the control group received no training. The data collection instrument was the work-family conflict questionnaire by Carlson et al. (2000). Data in the quantitative section were analyzed using repeated measures analysis of variance with the help of SPSS software. Findings: Given that the computed F-value for the effect of groups on work-family conflict and its dimensions was statistically significant at the 5% level (p < .05), it can be concluded that there was a significant difference between the experimental and control groups after the intervention, and the intervention significantly impacted work-family conflict and its dimensions. The Benferroni post-hoc test indicated that the effects of the educational program based on opportunities and threats of remote work on work-family conflict and its dimensions showed suitable stability during the follow-up phase. Conclusion: Therefore, it can be concluded that the educational package derived from the lived experiences of dual-career couples during the quarantine period of the COVID-19 outbreak was effective on the dimensions of work-family conflict among couples, and this effect was also stable in the follow-up phase.